Tingkat Pengetahuan dan Sikap Ibu terhadap Perkembangan Sensorik Motorik pada Balita di Desa Lambaro Sukon Tahun 2024 - Masyithah Masyithah; Syukriadi Syukriadi; Irma Andriani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Knowledge is the result of understanding or a state of knowing that arises after someone senses a certain object. A mother's attitude is a reaction or response that is still closed from a person to a stimulus or object. This research aims to determine the relationship between mothers' knowledge and attitudes towards sensory-motor development in toddlers in Lambaro Sukon Village, Aceh Besar. This research uses a quantitative approach with a cross-sectional design. The sample was selected using a total sampling technique with a total sample of 73 respondents. This research was conducted from 16th April – 11st July 2024. The data collection technique used a questionnaire with maternal knowledge and attitude questionnaire instruments as well as KPSP. Data analysis techniques use univariate and bivariate tests. The results of data analysis showed that the characteristics of mothers were dominated by mothers with sufficient knowledge who had toddlers with good sensory motor categories (58.1%). Most of the mother's attitude was obtained, namely a good mother's attitude with the child's sensory and motor skills being in the good category (57.8%). The results of hypothesis testing using Chi Square obtained a sig value. calculate mother's knowledge (p= 0.034), and mother's attitude (p= 0.001). Based on the results of the hypothesis test, it was concluded that there was a significant relationship between mothers' knowledge of toddlers' sensory-motor development and there was a significant relationship between mothers' attitudes towards toddlers' sensory-motor development. The suggestion in this research is that this research can provide more information to mothers about children's motor balance, as study material and knowledge that can help for further research activities.